Evaluation Of Knee Meniscal Tear Frequency In Symptomatic Patients Setting MRI As Gold Standard - Javed, Sana; Ali, Abid; Zulfiqar, Taiba (Medical Science Journal for Advance Research, 2022)
Background: Physical activities like sports gymnastics games, cycling, brisk walking, and running has always been a fun and important activities for people’s health and especially when it became their occupation. Due to increased unhealthy eating disorders in people, they have developed an unhealthy weight which is causing them to be weakened and causing pain especially at joints. For the diagnosis conventional radiography was never helpful because it is not for soft tissues whereas MRI is been using in muscoskeletal as modality of choice. Methods: total 600 patients were included in this prospective study with acute knee pain held at Lahore. 1.5 T MRI is used to rule out meniscal tears. Duration was of one year. Scans were reported by 2 expert radiologists and spss version 25.0 is used for frequency analysis. Asymptomatic patients were excluded from this study. Results: Knee meniscal tear frequency was ruled out in symptomatic patients including acute knee pain. Frequency was determined from 600 patients by determining male and female in them. Positive meniscal tear findings were discriminated by negative meniscal tear findings. Men has high ratio of meniscal tears because of many factors as compared to women. Conclusion: Jumping, supports, running and high intensity physical activities can be the cause of meniscal tear. Early evaluation of tear is necessary for the treatment of symptoms such as acute knee pain etc. Magnetic resonance imaging is non- invasive useful muscoskeletal imaging modality which can detect the tear even at very small grade such as grade 1.